2019
DOI: 10.22616/foodbalt.2019.050
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds in fresh and dried ginger root (Zingiber Officinale)

Abstract: Ginger (Zingiber officinale) is known as an additive for food and therapeutic purposes. It can help improve memory, helps eliminate toxins from the body, lowering arterial pressure and cholesterol, and is a good source of many bioactive compoundsphenolic s, vitamins and mineral elements. The aim of study was to determine biological active compounds of fresh and dried ginger in aqueous extracts. Spectrophotometric methods were used for determination content of total phenolic (according to the Folin-Ciocalteu me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…[9,10]. If a comparison is drawn on the basis of the phenolic profile, conventional solvent extraction using water and ethanol as solvents resulted in total phenolic contents of 104.7 ± 4.5 mg GAE/100 g and 650.44 ± 27.32 mg GAE/100 g of dry weight, respectively [31,32], while the extract of freeze-dried ginger powder produced through sonication came up with a total phenolic content of 931.94 ± 0.02 mg GAE/100 g of dry weight [27]. The chemical composition and yield of ginger extract and ginger essential oil are also influenced by the extraction method.…”
Section: Effect Of Processing and Extraction Process On Ginger Bioact...mentioning
confidence: 99%
“…[9,10]. If a comparison is drawn on the basis of the phenolic profile, conventional solvent extraction using water and ethanol as solvents resulted in total phenolic contents of 104.7 ± 4.5 mg GAE/100 g and 650.44 ± 27.32 mg GAE/100 g of dry weight, respectively [31,32], while the extract of freeze-dried ginger powder produced through sonication came up with a total phenolic content of 931.94 ± 0.02 mg GAE/100 g of dry weight [27]. The chemical composition and yield of ginger extract and ginger essential oil are also influenced by the extraction method.…”
Section: Effect Of Processing and Extraction Process On Ginger Bioact...mentioning
confidence: 99%
“…Additionally, ginger extract has high antioxidant activities, which keep the equilibrium between ROS and antioxidant resistance enzymes in testis cells (Banihani, 2019) Consequently, it may lead to the enhancement of the biosynthesis of testosterone hormone, and improvement of the male reproductive functions in rats. Based on our result (Ozola et al, 2019) reported that ginger includes numerous antioxidants involving vitamin C, flavonoids, and phenol elements, as well as indicated that ginger ethanol extract contains great concentrations of tannins and alkaloids and includes high levels of phenolic and flavonoid elements which displayed significant regained testis histopathological alterations. In conclusion.…”
Section: Discussionmentioning
confidence: 59%
“…The study aimed to evaluate the presence or absence of flavonoid and phenol compounds in the plant samples. These components are recognized as naturally occurring antioxidants with possible physiological and therapeutic applications [11].…”
Section: Qualitative Phytochemical Analysismentioning
confidence: 99%
“…The findings of the phytochemical screening are shown in Table 1, which shows that all leaf samples from the chosen plant species contained phenol and flavonoids. It is acknowledged that phenol and flavonoids play a crucial role in giving plants their antioxidant qualities [11]. Methanol was a strategically chosen solvent for the phytochemical screening process because of its high polarity, amphiphilic character, and capacity to extract a broad variety of chemical components from plants.…”
Section: Qualitative Phytochemical Analysismentioning
confidence: 99%